INVESTIGATION OF HIV-1 ANTISENSE TRANSCRIPT EXPRESSION IN VIVO - Sklutuis, Rachel (My University, 2022)
Natural antisense transcripts (NATs) are a class of RNA molecules that function in regulating gene expression and are transcribed from the opposite strand of some protein-coding genes. In Human Immunodeficiency virus 1 (HIV-1), in vitro experiments have shown that expression of a NAT called Ast promotes the establishment and maintenance of viral latency through polycomb repressive complex 2 (PRC2)-induced epigenetic regulation of viral gene expression. The levels of Ast expression in single infected cells isolated from donors on suppressive antiretroviral therapy (ART) was investigated with a cell-associated RNA and DNA single-genome sequencing (CARD-SGS) assay adapted to detect Ast RNA. Additionally, a digital Polymerase Chain Reaction (PCR) approach was used to examine both sense and antisense HIV-1 gene expression. A median of ~5% of infected cells contained Ast RNA when measured by CARD-SGS. Ast expression levels ranged from 1-30 RNA copies/cell. Ast RNA measured using the digital reverse transcription PCR (RT-PCR) approach was detected in up to a median of 26% of infected peripheral blood mononuclear cells (PBMC). A similar fraction of infected cells contained sense env RNA as antisense Ast RNA in most donor samples. These findings confirm expression of HIV-1 Ast RNA in donors on ART. Detection of Ast RNA in unstimulated cells from donors on ART warrants the investigation of its bifunctional role as a coding and a regulatory RNA in vivo.